Made by Hong Kong - edited by Suzanne Berger and Richard K. Lester; made by Hong Kong study leaders; Alice H. Amsden (Oxford University Press, 1997)
The authors suggest ways to develop while maintaining and enhancing production activities. They examine the role of biotechnology and information technology by bringing in international experts in these fields from the MIT research community and provide recommendations for government, industry, and academia